Dirty Marks / The Education of Self, Media and Popular Culture - Schostak John F (Pluto Press, 1993)
This book looks at the variety of ways in which we appear to learn about good and evil - about heroes and villains. Introduction, Happy Families: Knowledge and Ignorance and Innocence - the Drama Begins, Stepping Out Along the Course of Life, Heroes and Villains: Industrialized Culture and the Contortion of Experience, Forbidden Forms of Representation, Making the News: Duping and Smearing and Silencing, The Forbidden Politics and the Education of Challenge, Self Assertion and Violence, The Thatcher Years: No Turning Back, The Education of Action, References, Index.